The prevalence of hyaline membrane disease and the value of shake test and lamellar body concentration in preterm infants - Dzulfikar DLH; Ali Usman; Melinda D Nataprawira; Aris Primadi (Indonesian Pediatric Society Publishing House, 2016)
Background The morbidity and mortality of hyaline membrane dis- ease (HMD) are quite high due to delayed diagnosis and intervention. Commonly, HMD occurs in preterm infants with surfactant deficiency because of lung immaturity. Lung maturity test could be performed using biochemical, biophysical, and amniotic fluid turbidity test. Objective To find out HMD prevalence and the value of shake test and lamellar body concentration in diagnosing HMD in preterm infants. Methods This was a cross-sectional study carried out at Hasan Sadikin Hospital Bandung on preterm infants born during October- December 2001. The shake test was performed using gastric fluid and amniotic fluid while the lamellar body concentration was per- formed using amniotic fluid. Results During the 3-month period, 571 infants were born, of 64 (11.2%) preterm infants, only 41 (64%) fulfilled the inclusion crite- ria; among those preterm infants, 14 (34%) suffered from respira- tory distress and 7 suffered from HMD (prevalence 17%). All HMD cases occurred in infants less than 32 weeks for gestational age. In 7 preterm infants with HMD, the shake test of gastric fluid ob- tained by lavage showed negative results in 3 and +1 in 4 infants; while the shake test of amniotic fluid revealed negative result in 5 and +1 in 2 infants. Lamellar body concentration of amniotic fluid was ≤18,000/ml in all HMD infants. Among three infants less than 32 weeks for gestational age who did not suffer from HMD, +1 shake test of gastric fluid was found in 2 infants and +2 in 1 infant; while shake test of amniotic fluid showed negative result in 1 infant and +1 in 2; the lamellar body concentration of amniotic fluid was ≤18,000/ml in 2 infants and >18,000/ml in 1 infant. Conclusions We concluded that HMD occurred in 17% of preterm infants. The shake test of gastric and amniotic fluids revealed nega- tive or +1 results whereas lamellar body concentration had value of less than or equal to 18,000/mL. More extensive studies are warranted to assess the validity (sensitivity, specificity and predic- tive values) of these measurements